Motor development in infancy and spine shape in early old age: Findings from a British birth cohort study. Issue 12 (18th March 2020) - Saunders, Fiona R.; Gregory, Jennifer S.; Pavlova, Anastasia V.; Muthuri, Stella G.; Hardy, Rebecca J.; Martin, Kathryn R.; Barr, Rebecca J.; Adams, Judith E.; Kuh, Diana; Aspden, Richard M.; Cooper, Rachel; Ireland, Alex
Abstract: Spine shape changes dramatically in early life, influenced by attainment of developmental milestones such as independent walking. Whether these associations persist across life is unknown. Therefore, we investigated associations between developmental milestones and spine shape, as determined using statistical shape models (SSMs) of lumbar spine from dual‐energy X‐ray absorptiometry scans in 1327 individuals (688 female) at 60 to 64 years in the MRC National Survey of Health and Development. Lumbar lordosis angle (L4 inferior endplate to T12 superior endplate) was measured using the two‐line Cobb method. In analyses adjusted for sex, height, lean and fat mass, socioeconomic position, and birthweight, later walking age was associated with greater lordosis described by SSM1 (regression coefficient, 0.023; 95% CI, 0.000‐0.047; P = .05) and direct angle measurement. Modest associations between walking age and less variation in anterior‐posterior vertebral size caudally (SSM6) were also observed (0.021; 95% CI, −0.002 to 0.044; P = .07). Sex interactions showed that later walking was associated with larger relative vertebral anterior‐posterior dimensions in men (SSM3; −0.043; 95% CI, −0.075 to 0.01; P = .01) but not women (0.018; 95% CI, −0.0007 to 0.043; P = .17). Similar associations were observed between age at independent standing and SSMs but there was little evidence of association between sitting age and spine shape. Unadjusted associations between walking age and SSMs 1 and 6 remained similar after adjustment for potential confounders and mediators. This suggests that these associations may be explained by altered mechanical loading of the spine during childhood growth, although other factors could contribute. Early life motor development, particularly walking, may have a lasting effect on the features of spine morphology with clinical significance.